Conceptualising Brand Charisma - Hatton-Jones, Siobhan; Teah, Hui Min; Phau, Yong Ian (2017)
The conceptualisation of brand charisma is multi-disciplinary, using luxury branding context. This research adds value by making significant contributions by extending and building theory; holds managerial implications for policymakers and brand managers in shaping and communicating brand charisma; additionally to develop a research framework and scale to measure brand charisma.